The validity of floating chambers in quantifying CO2 flux from headwater streams - M. J. Rawitch (IWA Publishing, 2021)
The amount of CO2 exiting headwater streams through degassing plays an important role in the global carbon cycle, yet quantification of CO2 degassing remains challenging because of the morphology of headwater streams and because of uncertainty about whether floating or suspended chambers provide valid measurements in moving water. We show that experiments using large and small floating chambers in flowing water over a moderate range of water velocities (0.13–0.23 m s−1) in a laboratory flume resulted in similar k600s to published field measurements with similar water velocities. We confirmed the flume experiments with paired stirred-still beaker experiments, where resulting k600s fell within the extrapolated trend of the flume experiments. We propose that the floating chambers can provide good estimates of CO2 degassing, particularly in shallow, low-velocity, morphologically complex headwater streams, permitting quantification of this important contributor to the global carbon cycle. HIGHLIGHTS Headwater streams contribute significantly to the C efflux from inland waters, yet the size of their contribution has only recently begun to be quantified.; Floating chambers, to date, are only generally accepted for use in relatively still waters (lakes, oceans), yet are increasingly used in characterizing headwater streams. Thus, we designed laboratory experiments to compare CO2 degassing using a floating chamber in a flume, with other methods of quantifying degassing rates.; In our experiments, k600-CO2 values varied linearly with water velocities from 0.13 to 0.23 m s−1, velocities that are typical of headwater streams. This confirms the importance of water velocity-induced turbulence to k600-CO2. It was not clear whether floating chamber design strongly affected the k600-CO2 results.; We compared CO2 degassing in floating chambers to calculated CO2 degassing based on the pH increase in stirred beakers of flume water, and found that the beaker experiments, although at lower water velocities, fell on the extended trend of the flume experiments.; These results support the use of floating chambers to characterize CO2 degassing in headwater stream type environments.;